1993
DOI: 10.1016/s1057-7408(08)80021-6
|View full text |Cite
|
Sign up to set email alerts
|

An approach to investigating the emotional determinants of consumption durations: Why do people consume what they consume for as long as they consume it?

Abstract: Previous work in consumer research has left questions concerning the duration of consumption largely unexplored and, in particular, has neglected the possible role of emotions in determining the length of time that consumers devote to consumption experiences. This study proposes an approach to investigating these questions and illustrates its application to the context of examining the connection between emotional responses and listening receptivity to music. Specifically, Russell, Weiss, and Mendelsohn's (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(53 citation statements)
references
References 32 publications
2
47
1
3
Order By: Relevance
“…In a similar fashion, Vida et al (2007) found that music that is perceived to fit the store image had a positive affect on the length of shopping time, which indirectly influenced consumers' expenditure. In sum, music appears to impact a variety of dependent variables, such as affective ones (mood, arousal pleasure, emotion) (Bitner, 1992;Tansik and Routhieaux, 1999), financial returns (value of sales, quantity purchased, gross margins) (North et al, 2000(North et al, , 2003, attitudes and perception (liking, brand loyalty, service quality) (Chebat and Gelinas-Chebat, 1993;Grewal et al, 2003), temporal effects (duration perceived/actual, time to consume) (Holbrook and Gardner, 1993), and behavioral variables (patronage frequency, store choice, in-store traffic flow) (Turley and Milliman, 2000;Garlin and Owen, 2006).…”
Section: Previous Research and Hypotheses Developmentmentioning
confidence: 99%
“…In a similar fashion, Vida et al (2007) found that music that is perceived to fit the store image had a positive affect on the length of shopping time, which indirectly influenced consumers' expenditure. In sum, music appears to impact a variety of dependent variables, such as affective ones (mood, arousal pleasure, emotion) (Bitner, 1992;Tansik and Routhieaux, 1999), financial returns (value of sales, quantity purchased, gross margins) (North et al, 2000(North et al, , 2003, attitudes and perception (liking, brand loyalty, service quality) (Chebat and Gelinas-Chebat, 1993;Grewal et al, 2003), temporal effects (duration perceived/actual, time to consume) (Holbrook and Gardner, 1993), and behavioral variables (patronage frequency, store choice, in-store traffic flow) (Turley and Milliman, 2000;Garlin and Owen, 2006).…”
Section: Previous Research and Hypotheses Developmentmentioning
confidence: 99%
“…Music itself has been the subject of a lot of research regarding its use in advertising (e.g., Alpert & Alpert, 1989;MacInnis & Park, 1991) and in classical conditioning (e.g., Kellaris & Cox, 1989) as well as regarding its effects on purchasing behaviour (e.g., Milliman, 1982). Certain studies have also looked at the aesthetic dimensions of music (e.g., Holbrook, 1982) or at the effects of tempo on behavioural intentions and emotional arousal (e.g., Holbrook & Gardner, 1993). However, although music fi gures importantly in the lifestyles of many people (Konečni, 1982), no study explores the music-related factors that explain why people choose to either purchase music (Lacher & Mizerski, 1994), download music, or listen to music without feeling compelled to own it.…”
Section: à Partir D'enquêtes Qualitatives Et Quantitatives Nous Montmentioning
confidence: 99%
“…: Holbrook, 1982) ou aux effets du tempo sur les intentions de comportement et l'éveil émotionnel (ex. : Holbrook & Gardner, 1993). Cependant, bien qu'elle soit une composante majeure du style de vie d'un grand nombre d'individus (Koneč ni, 1982), aucune étude n'explore les facteurs relatifs aux oeuvres musicales expliquant pourquoi les gens choisissent soit d'acheter la musique (Lacher & Mizerski, 1994), soit de la télécharger, soit encore de l'écouter tout simplement sans ressentir le besoin d'en faire l'acquisition.…”
Section: A Partir D'enquêtes Qualitatives Et Quantitatives Nous Montunclassified